If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.7(-0.62 + -4x) = 33x (-0.62 * -0.7 + -4x * -0.7) = 33x (0.434 + 2.8x) = 33x Solving 0.434 + 2.8x = 33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33x' to each side of the equation. 0.434 + 2.8x + -33x = 33x + -33x Combine like terms: 2.8x + -33x = -30.2x 0.434 + -30.2x = 33x + -33x Combine like terms: 33x + -33x = 0 0.434 + -30.2x = 0 Add '-0.434' to each side of the equation. 0.434 + -0.434 + -30.2x = 0 + -0.434 Combine like terms: 0.434 + -0.434 = 0.000 0.000 + -30.2x = 0 + -0.434 -30.2x = 0 + -0.434 Combine like terms: 0 + -0.434 = -0.434 -30.2x = -0.434 Divide each side by '-30.2'. x = 0.01437086093 Simplifying x = 0.01437086093
| -2w=21+w | | 2=3+.25n | | -5(y+3)=-2y+3 | | -3x-1=8-3 | | 2x-23=30 | | -0.33333333x=12 | | -15y=-8 | | 5x^2+12x=-4x^2-4 | | gx=x^2-10x+11 | | 5(x-2)=-9 | | 95-4x=41x+15 | | 3x+16=x-10 | | fx=x^2+6x-3 | | X-2(2X+3)=0 | | 4v-2v=4 | | 2w+5=5-25 | | 14x^2-23xy+3y^2=0 | | 5x-1=x+3 | | 2x/5+3=9 | | 6(x+7)-20=9x | | 2(3w-7)=16 | | 7y-4=15+3 | | 3y^5+9y^2= | | Ax=y+k | | 7-1/9=32k | | 4=-3x+5 | | Ax=y+3 | | 7-1/9=32 | | 5a+9b-3a-4b= | | 49=4x+17 | | 3(5y-7)-6=24 | | 3(5y-7)-6=25 |